An intact histone 3'-processing site is required for transcription termination in a mouse histone H2a gene. - Chodchoy, N (1991)
A transcription termination site has been characterized between the mouse histone H2a-614 and H3-614 genes. There is a poly(A)- RNA present in small amounts in the nucleus which ends 600 nucleotides 3' to the H2a-614 gene. Nuclear transcription studies demonstrate that transcription extends at least 600 nucleotides 3' to the gene but is greatly reduced 700 nucleotides 3' to the gene. If all or part of the normal 3'-processing signal, consisting of the stem-loop and the U7 small nuclear ribonucleoprotein binding site, is deleted, transcription then continues past the putative termination site and RNAs which end at the 3' end of the downstream H3-614 gene accumulate. Insertion of a 150-nucleotide fragment containing the termination site between the histone 3' end and downstream polyadenylation sites reduces usage of polyadenylation sites 85 to 90%. Taken together these results suggest there is a transcription termination site which requires an intact histone 3'-processing signal to function.